New Galactic Planetary nebulae selected by radio and multiwavelength characteristics. Issue 3 (25th July 2018) - Fragkou, V; Parker, Q A; Bojičić, I S; Aksaker, N
ABSTRACT: We have used the Cornish radio catalogue combined with the use of multiwavelength data to identify 62 new Planetary Nebula (PN) candidates close to the Galactic mid-plane. Of this sample 11 have weak optical counterparts in deep narrow band Hα imaging that allows their spectroscopic follow-up. We have observed eight of these candidates spectroscopically, leading to the confirmation of seven out of eight as PNe. All but one of our sample of newly detected PNe appear to be of Type I chemistry with very large [N ii ]/Hα ratios. This indicates that our selection method heavily favours detection of this kind of PN. Cornish is a low-Galactic latitude survey where young objects and Type I PNe (thought to derive from higher mass progenitors) are more plentiful, but where optical extinction is large. The very high success rate in correctly identifying PNe in this zone proves the efficacy of our radio and multiple multiwavelength diagnostic tools used to successfully predict and then confirm their PN nature, at least in the cases where an optical counterpart is found and has been observed. The study reinforces the effective use of a combination of multiwavelength and optical data in the identification of new Galactic PNe and especially those of Type I chemistries whose dusty environments often prevents their easy detection in the optical regime alone.